Do firms adjust toward a target leverage level? - Zhaoxia Xu (Bank of Canada, 2007)
This paper studies capital structure adjustment mechanisms of firms that experience substantial changes in leverage. Adjustments appear to be asymmetric among firms with large increases and those with large decreases in debt ratios. The different adjustments are not due to differences in leverage targets or industry distributions between the samples. Speeds of adjustment are found to be affected by market timing opportunities. The persistence of equity market timing opportunities slows some firms' rebalancing process.
Keywords: G32; 330; Financial markets; International topics; Kapitalstruktur; Eigenkapital; Fremdkapital; Kapitalkosten; Wertpapieremission; Welt